2017
DOI: 10.1149/2.0141711jes
|View full text |Cite
|
Sign up to set email alerts
|

Model Based Analysis of One-Dimensional Oriented Lithium-Ion Battery Electrodes

Abstract: Oriented one-dimensional nanostructures have been of substantial interest as electrodes for lithium-ion batteries due to the better performance both in terms of initial capacity and lower capacity fade compared to powder pressed electrodes. This paper focuses on a model driven approach to understanding the relationship between the morphology of these oriented nanostructures to the performance of the battery. The Newman-type P2D modeling technique is applied to a porous electrode made up with solid continuous c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…367 In search for the optimal particle distribution inside the electrodes, Chadha et al have explored the properties of onedimensional (columnar) structures on the overall transport in TiO 2 based electrodes. 368 The Newman's approach is used whereby the transport in solid cylinder is modeled in axial and radial directions, but no phase transformation was included. The authors identified, thanks to their model, optimal column lengths and column spacing as a function of the discharge rate.…”
Section: Volume Averaging Methodsmentioning
confidence: 99%
“…367 In search for the optimal particle distribution inside the electrodes, Chadha et al have explored the properties of onedimensional (columnar) structures on the overall transport in TiO 2 based electrodes. 368 The Newman's approach is used whereby the transport in solid cylinder is modeled in axial and radial directions, but no phase transformation was included. The authors identified, thanks to their model, optimal column lengths and column spacing as a function of the discharge rate.…”
Section: Volume Averaging Methodsmentioning
confidence: 99%
“…Nevertheless, equivalent porous medium model ignores the microstructure of electrodes. Then, Newman et al 31,32 develop the pseudo two-dimensional (P2D) model to study charging process 33 and thermal effect 34 of lithium ion battery. P2D model simulates the intercalation/ deintercalation process by assuming active material as isotropic spherical particles of uniform size.…”
mentioning
confidence: 99%
“…We also found that whether it is before and after electrochemical reaction, it follows such rule: R particles > R NWs > R GNCs , the diffusion ability of ions follows the same rule. The results show that 1D nanostructures have better charge and ion transport capabilities than particle structures . The addition of graphene can further enhance the ability of charge transfer and ion transfer …”
Section: Resultsmentioning
confidence: 97%